Tinjauan Yuridis Perjanjian Asuransi Laut bagi Penumpang Kapal Laut - Sylviana Ayu Retno Ambarsari (Perspektif Hukum, 2015)
The ship as a means to transport passengers before sailing should legally have been stated in seaworthy condition that must fulfill safety requirements and shipping standards of the ship. The unseaworthy stipulated ship would have undergone ship wreck. Therefore, can the passengers’ ticket be evidence to claim assurance when ship wreck occurs. Furthermore, how accountability of ship owner for the occurred Dumai Express 10 ship wreck is. The research constitutes normatively legal research that uses statute approach. The result shows that the passengers’ ticket can be evidence to claim the assurance. When the ship wreck happens, the passenger has the right to obtain indemnity or compensation the transporters have to pay because of the transporters’ negligence as long as transporting the passengers. There are two reasons for paying indemnity, namely damaging the contract and acting the unlawful deeds. The indemnity for damaging the contract is stipulated from Article 1246 to Article 1252 of Book III of the Civil Code, while the indemnity for unlawful deeds is stipulated in Article 1365 of the Civil Code. Thus, the issue, Dumai Express 10 Ship undergoes, constitutes the compensation for damaging the contract.